The Douro estuary: modelling comparison for floods prevention - Iglesias, I. (2016)
Estuarine areas have been intensively studied due to their complex physical processes and the societal importance of their ecosystem services. To perform a deeper hydrodynamic study allowing an accurate representation of the physical processes, numerical models are essential. This work performs a comparison of the two 2DH estuarine models, included in the modelling suites OpenTelemac and Delft3D. The aim is to understand how the different numerical schemes might influence the models’ output. The models were applied to one of the main Portuguese estuaries: the Douro River estuary. The strong floods that the estuarine region periodically suffers, with economic losses and damages to the local protected landscape areas and hydraulic structures, show the importance of a complete characterization of the areas at risk and how they might be affected. Both models were configured with the same initial and boundary conditions and similar bathymetries. The simulations presented herein use a pre-breakwater construction configuration. However, a postbreakwater construction configuration was also defined and results will be presented at the conference. A special interest will be attached to the role of the Cabedelo sandbar, as this is expected to break for strong river discharges thus diminishing the flooding risk.